A Person-Centered Approach Understanding Stroke Survivor and Family Caregiver Emotional Health. Issue 2 (11th April 2022) - Varughese, Tina; Casameni Montiel, Tahani; Engebretson, Joan; Savitz, Sean I.; Sharrief, Anjail; Beauchamp, Jennifer E. S.
Abstract : Supplemental digital content is available in the text. ABSTRACT: BACKGROUND: The purpose of this study was to incorporate a person-centered approach to understand the emotional health needs and perspectives of stroke survivors (SSs) and their caregivers. METHODS: In collaboration with 4 SSs and caregivers as research partners, quantitative data were collected to assess poststroke emotional health needs, and qualitative data were collected to gain insight into SS and caregiver emotional health perspectives after stroke. RESULTS: Forty surveys (n = 26 SSs, n = 14 caregivers) were collected. The predominate emotional health needs were frustration (65%), anxiety (54%), and stress (50%) for SSs and stress (71%), worry (57%), and frustration (57%) for caregivers. Two group interviews (n = 7 SSs, n = 3 caregivers) were completed. Four emerging themes were identified: receiving support from those in similar situations, poststroke emotional responses, situations experienced in healthcare settings, and a hypervigilance for sudden and unexpected events. CONCLUSION: Emotional healthcare services for SSs and their caregivers may consider providing reoccurring mental health education and multifaceted treatment approaches, including provision of peer support, and addressing the unique emotional stressors SSs and caregivers may be experiencing. The small sample size precludes generalizing the results into the broader stroke population. However, by leveraging the lived experience of SSs and their caregivers, the results may help find ways to support SSs' and caregivers' emotional health.